Chemical Utilization of Wood : its Opportunities and Obstacles - Stamm, Alfred J. (Indian Forester, 1947)
chemical utilization of wood has been discussed in seversl articles in previous issues of the JOURNAL OF FORESTRY, but in none of these has the subject been treated as comprehensively as in the following paper, which covers pulping, extraction, hydrolysis, destructive distillation, reactions with other chemicals, and chemical treatments to improve the properties of wood. The author points out that no universally successful method of utilizing inferior waste wood has yet been discovered, but that developments to date make the future look encouraging. One unsolved problem is that of cheap transportation of large quantities of waste to processing plants. The chemist looks to the forester to solve this problem.